Perancangan Aksesibilitas Penyandang Disabilitas Fisik pada Workshop Ability Hub: bahasa indonesia - I Wayan Darma Yasa; I Wayan Wirya Sastrawan; Agus Kurniawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The Head of the Office for Village Community Empowerment, Population and Civil Registration of the Province of Bali, said that 12,086 residents with disabilities in the Province of Bali and the dominant age of 18 years and over around 10,703 or (88.56%). Of the many persons with disabilities in Bali, it is necessary to support programs and activities related to the principle of disability equality that are carried out in a comprehensive and sustainable manner supported by special facilities and infrastructure for persons with disabilities. The research method used by the author is qualitative with inductive and thoroughly oriented to historical processes, ethnography and case studies that have been passed and described descriptively by the phenomena to be studied, based on the results of personal notes, field notes, and literature studies. Based on process analysis on a review of the accessibility system for persons with disabilities to describe the ease of reaching users of buildings. This design focuses on accessibility issues and building attainment starting from parking, main entrance, pedestrian, building entrance, connecting circulation between buildings and circulation of space.